2016
DOI: 10.1021/jacs.6b03899
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (+)-7,20-Diisocyanoadociane and Liver-Stage Antiplasmodial Activity of the Isocyanoterpene Class

Abstract: 7,20-Diisocyanoadociane, a scarce marine metabolite with potent antimalarial activity, was synthesized as a single enantiomer in 13 steps from simple building blocks (17 linear steps). Chemical synthesis enabled identification of ICT antiplasmodial activity against liver-stage parasites, which suggested heme detoxification does not exclusively underlie the mechanism of action of this class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 46 publications
1
55
0
1
Order By: Relevance
“…Appealing to academia and industry, transfer hydrogenation (TH) as an alternative protocol avoiding the necessity of flammable hydrogen gas has received extensive attention in recent decades. Achievements have been devoted to discovering novel hydrogen donors and realizing special configuration control in total synthesis of natural products; however, water as an ideal hydrogen atom source, namely hydrogen atom transfer (HAT), with the merits of environmental acceptability, safety, and cost‐benefits has been less investigated . In 2006, Cuerva and co‐workers revealed the first titanocene‐catalyzed reduction of epoxides with water as the hydrogen atom source through a radical pathway (Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…Appealing to academia and industry, transfer hydrogenation (TH) as an alternative protocol avoiding the necessity of flammable hydrogen gas has received extensive attention in recent decades. Achievements have been devoted to discovering novel hydrogen donors and realizing special configuration control in total synthesis of natural products; however, water as an ideal hydrogen atom source, namely hydrogen atom transfer (HAT), with the merits of environmental acceptability, safety, and cost‐benefits has been less investigated . In 2006, Cuerva and co‐workers revealed the first titanocene‐catalyzed reduction of epoxides with water as the hydrogen atom source through a radical pathway (Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…[14] Presented with this opportunity for discovery,w ee mbarked upon as creen of combinations of different methyl organometallic reagents,L ewis acids additives,s olvents,a nd cosolvents,while simultaneously studying classical literature on carbonyl additions.I nt his way,a nd with guidance from the critical studies of Ashby and co-workers, [19] we found that an excess of trimethylaluminum in solvents of low polarity tended to favor the generation of the desired axially methylated adduct 8.T od ate,w eh ave managed selectivities of 2-2.5:1, but the trivial separation of the resulting diastereomers,t he avoidance of stoichiometric mercury reagents, and the identical yield to the multi-step solution of Shenvi make this an attractive alternative.C onversion of 8 to 1 by application of the invertive isocyanation protocol of Shenvi afforded the natural product exactly as described. TheS henvi group reported that their efforts to do so were unsuccessful, opting instead for amulti-step but highly diastereoselective sequence of Peterson olefination and oxymercuration/reduction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[9] Indeed, this strategy was central to our synthesis of kalihinol B( 2), [4] many simplified yet active kalihinol analogues, [5] and our previous formal synthesis of DICA( 1). [6a] Tw ot otal syntheses sought to solve the stereocontrol conundrum at the C7 and C20 isonitrile-bearing carbons:t he approach of Fairweather and Mander used stereospecific Curtius rearrangements to install tertiary carbinolamines as isonitrile precursors, [13] and the synthesis of the Shenvi group [14] featured their method for invertive displacement of tertiary trifluoroacetates (TMSCN, Sc(OTf) 3 )o nt he bis-trifluoroacetate derived from 8,w hich provided astereoselective counterpoint to the endgame from 7. [10] Double equatorial nucleophilic methylation, activation by trifluoroacetylation and treatment with TMSCN and TiCl 4 led to stereochemically uncontrolled formation of 1 and its three stereoisomers.Several subsequent formal syntheses were based on the formation of the Corey dione,a nd thus inherited its troublesome endgame.T hese achievements include aD iels-Alder approach strategically similar to Coreysf rom the Miyaoka group, [11] an oxidative enolate coupling/ring-closing metathesis approach from Robinson and Thomson [12] and our own conjugate addition/ enolate trapping strategy.…”
mentioning
confidence: 99%
“…For example, our discovery that the amphilectenes and adocianes are cytotoxic against liver-stage parasites militates against heme detoxification inhibition as the exclusive antiplasmodial mechanism. 6 Copper chelation is simply not possible for congeners with distant isonitriles. As part of a program to investigate the biological activity of ICTs, we have begun to develop effective chemical syntheses 2,6,7 and associated methods 8 to produce and modify three main structural classes: amphilectenes, adocianes, and kalihinols.…”
mentioning
confidence: 99%
“…6 Copper chelation is simply not possible for congeners with distant isonitriles. As part of a program to investigate the biological activity of ICTs, we have begun to develop effective chemical syntheses 2,6,7 and associated methods 8 to produce and modify three main structural classes: amphilectenes, adocianes, and kalihinols. 1,2 Prior syntheses 9 of the kalihinol class have fought to control stereochemistry in the functionally dense scaffolds, and each contains at least one uncontrolled ( ca.…”
mentioning
confidence: 99%